Аналіз сучасних методів і підходів до математичного моделювання та оптимізіції параметрів технологічних процесів в енергетичному устаткуванні енергоблоків ТЕС і АЕС - Єфімов, Олександр В'ячеславович; Тютюник, Лариса Іванівна; Каверцев, Валерій Леонідович; Гаркуша, Тетяна Анатоліївна; Мотовільнік, Анастасія Вадимівна; Ліфшиць, Петро Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2020)
У матеріалах статті розглянуті класифікація сучасних методів системного аналізу, основні положення теорії і засобів математичного моделювання технологічних процесів в енергетичному устаткуванні, що призначені для автоматизованого управління складними теплоенергетичними системами. Розглянуті методи і підходи до математичного моделювання та оптимізації параметрів технологічних процесів в енергоблоках теплових (ТЕС) та атомних електростанцій (АЕС).

The materials of the article consider the classification of modern methods of system analysis, the main provisions of the theory and means of mathematical modeling of technological processes in power equipment, designed for automated control of complex thermal power systems. To consider methods and approaches to mathematical modeling and optimization of process parameters in TPP (thermal power plants) and NPP (nuclear power plants) power units. Modern steam turbine power units of thermal and nuclear power plants are complex technical, thermal power systems. Complex thermal power system is a set of interconnected and interacting elements and subsystems of different technological purposes, which form an inseparable whole, providing the system of some complex function in the form of electricity and heat production and which are described by a rather complex mathematical model. The theory of system analysis and mathematical modeling is widely used to select the structures and parameters of the technological processes of power units. Analysis of literature sources on the existing methods of mathematical modeling and selection criteria, schemes of technological processes and approaches to creating mathematical models of the functional state of steam turbine power units, showed the need to improve them to take into account operational reliability.
Analysis modern methods and approaches to simulation modeling optimization of process parameters in power equipment thermal power plants and nuclear power plants
Keywords: математичне моделювання; mathematical modeling